2020
DOI: 10.1016/j.jsxm.2020.05.025
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging–Based 3-Dimensional Pelvic Prototype Models to Improve Education Regarding Sexual Anatomy and Physiology

Abstract: Background Myths, misconceptions, and taboos about sexual anatomy and physiology are common and can affect sexual health and maintain harmful practices and beliefs. Aim To construct a female and a preliminary male 3-dimensional (3D) pelvic model on the basis of in vivo imaging, which could be studied in sex education and clinical practice. Methods We retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Since most of the participants were recruited at the FGM/C outpatient clinic where they had access to Table 4 FGSIS 1 mean scores of our sample and from the literature [30] 1 Female Genital Self-Image Scale Our study sample showed a positive genital self-image and a satisfactory sexual function and quality. Possible positive sociocultural beliefs associated with FGM/C [5,6] could explain the positive genital self-image and 13.9 ± 19.9 to be able to overcome the "anatomical damage", such as the enhancement of stimuli originating from other body areas, or through positive emotions, cultural values and fantasies [42][43][44][45]. Non-sexually active participants mostly attributed their sexual inactivity to the absence of a partner and not to a health condition, yet their scores suggest that their sexual inactivity and poor sexual quality might also be linked to a medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the participants were recruited at the FGM/C outpatient clinic where they had access to Table 4 FGSIS 1 mean scores of our sample and from the literature [30] 1 Female Genital Self-Image Scale Our study sample showed a positive genital self-image and a satisfactory sexual function and quality. Possible positive sociocultural beliefs associated with FGM/C [5,6] could explain the positive genital self-image and 13.9 ± 19.9 to be able to overcome the "anatomical damage", such as the enhancement of stimuli originating from other body areas, or through positive emotions, cultural values and fantasies [42][43][44][45]. Non-sexually active participants mostly attributed their sexual inactivity to the absence of a partner and not to a health condition, yet their scores suggest that their sexual inactivity and poor sexual quality might also be linked to a medical condition.…”
Section: Discussionmentioning
confidence: 99%
“…3D-printed pelvic models based on in vivo imaging can also be used for educational purposes among health professionals and sex educators. A novel 3D-printed educational anatomic kit created by Abdulcadir et al demonstrates models of female and male reproductive anatomy permitting the representation of variations in sex development and morphology, including models of clitorises of women who have undergone female genital mutilation, all of which are based on in vivo imaging [ 198 ]. 3DP can also supplement simulation-based medical education, which has a unique place in postgraduate gynecological training.…”
Section: Surgical Applicationsmentioning
confidence: 99%
“…Addressing this topic, like any other health matter, can reassure children and adolescents, who learn that any type of question can receive evidence‐based information in a confidential, safe and professional environment. Involving the patient while examining the genitalia by offering to look into a mirror or by using drawings or 3D models can help them understand genital anatomy 39 …”
Section: Importance Of Education By the Paediatricianmentioning
confidence: 99%